PENGARUH GOOD CORPORATE GOVERNANCE (GCG), RASIO BEBAN KLAIM, DAN RASIO PERTUMBUHAN PREMI TERHADAP TINGKAT SOLVABILITAS TAKAFUL MALAYSIA - DINDA ALYA ARYANI; ZUBAIDAH NASUTION; SURYA SETIAWAN (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2023)
This research aims to analyze the influence of Good Corporate Governance, Claim Expense Ratio, and Premium Growth Ratio on the Solvency Level of Malaysian Takaful. This study uses a quantitative approach using secondary data. The population of this study is all takaful companies in Malaysia with the 2016- 2021 research period. The sampling technique used was the purposive sampling method. Samples that met the criteria were 11 family takaful companies in Malaysia out of 11 family takaful companies in Malaysia. The model used as an analysis tool is multiple linear regression. Data processing in this study uses the SPSS 25 tool. The results of this study indicate that simultaneously the variables Executive Director, Non-Executive Director, Claim Expense Ratio, and Premium Growth Ratio have a positive and significant effect on Takaful Solvability (RBC) Families in Malaysia. In contrast, partial Executive Director has a negative and significant effect, Non-Executive Director has a positive and significant effect, and Claims expense ratio and premium growth ratio have no significant effect on risk-based capital (RBC) because the size of the claim expense does not affect the number of premiums received by insurance participants, which are included in the tabarru' fund which can only be used for the benefit of takaful participants so that they do not affect the amount of profit and retained earnings on equity.